The Link Between the Microbiota and HER2+ Breast Cancer: The New Challenge of Precision Medicine - Di Modica, Martina; Arlotta, Valeria; Sfondrini, Lucia; Tagliabue, Elda; Triulzi, Tiziana (Frontiers in Oncology, 2022)
The microbiota is emerging as a key player in cancer due to its involvement in several host physiological functions, including digestion, development of the immune system, and modulation of endocrine function. Moreover, its participation in the efficacy of anticancer treatments has been well described. For instance, the involvement of the breast microbiota in breast cancer (BC) development and progression has gained ground in the past several years. In this review, we report and discuss new findings on the impact of the gut and breast microbiota on BC, focusing on the HER2+ BC subtype, and the possibility of defining microbial signatures that are associated with disease aggressiveness, treatment response, and therapy toxicity. We also discuss novel insights into the mechanisms through which microorganism-host interactions occur and the possibility of microbiota editing in the prevention and treatment optimization of BC.